2019
DOI: 10.1093/rheumatology/kez228
|View full text |Cite
|
Sign up to set email alerts
|

PD-1+CXCR5−CD4+T cells are correlated with the severity of systemic lupus erythematosus

Abstract: Objectives PD-1+CXCR5−CD4+T peripheral helper (Tph) cells, a recently identified T cell subset, are proven to promote B cell responses and antibody production in rheumatoid arthritis, but their role in the pathogenesis of SLE is unknown. We explored the role of Tph in lupus disease development. Methods This cohort study included 68 patients with SLE and 41 age- and sex-matched healthy individuals. The frequency of PD-1+CXCR5−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 13 publications
4
88
0
Order By: Relevance
“…In line with this observation, the titers of islet autoantibodies were gradually decreased and seroconversion occurred in some patients with a long duration of T1D. 58,59 Whether Tph cells have a role in the pathogenesis of T1D requires further studies. 51 Meanwhile, the number of TFR cells were significantly decreased in T1D patient and first-degree relatives (FDR) of T1D patients, which could be reversed by rituximab treatment.…”
Section: The Aberrant Differentiation and Function Of Tfh Cells In T1dmentioning
confidence: 58%
“…In line with this observation, the titers of islet autoantibodies were gradually decreased and seroconversion occurred in some patients with a long duration of T1D. 58,59 Whether Tph cells have a role in the pathogenesis of T1D requires further studies. 51 Meanwhile, the number of TFR cells were significantly decreased in T1D patient and first-degree relatives (FDR) of T1D patients, which could be reversed by rituximab treatment.…”
Section: The Aberrant Differentiation and Function Of Tfh Cells In T1dmentioning
confidence: 58%
“…15 Similarly, cTph cells coexpressing other activation markers, such as CD38 and MHC class II, were increased in patients with systemic lupus erythematosus (SLE). [27][28][29] The frequency of cTph cells in SLE is positively correlated with anti-dsDNA titers, disease activity scores such as SLEDAI, and the frequencies of plasma cells/plasmablasts. [27][28][29] cTph cells in SLE exhibited B cell helper activities by producing IL-21, 29 IL-10, and succinate.…”
Section: Circulating Tph Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…For example, in inflamed synovial tissues in rheumatoid arthritis, CD4 + T cells that lack CXCR5 but express PD-1 hi and CCR2 (named peripheral helper T cells: Tph) induce memory B cells to differentiate into ASCs in a manner dependent on IL-21 and ICOS [59]. Recent studies showed an increase of CXCR5 − PD-1 hi Tph cells expressing CXCR3 in the blood of active SLE patients [60,61]. Similar to Tph cells in inflamed synovial tissues in rheumatoid arthritis, Lin et al showed that the blood Tph cells in SLE expressed high IL-21 and IFN-γ, and the frequency in the blood correlated with disease activity [60].…”
Section: Cd4 + T-cell Subsets Promoting the Cd11c + Dn B Cell Activitymentioning
confidence: 99%
“…Recent studies showed an increase of CXCR5 − PD-1 hi Tph cells expressing CXCR3 in the blood of active SLE patients [60,61]. Similar to Tph cells in inflamed synovial tissues in rheumatoid arthritis, Lin et al showed that the blood Tph cells in SLE expressed high IL-21 and IFN-γ, and the frequency in the blood correlated with disease activity [60]. By contrast, Caielli et al showed that CXCR3 + Tph cells in SLE patients expressed high IL-10, IFN-γ, and succinate, but no IL-21 or CXCL13, and provided help to B cells in a manner dependent on IL-10 and succinate [61].…”
Section: Cd4 + T-cell Subsets Promoting the Cd11c + Dn B Cell Activitymentioning
confidence: 99%
See 1 more Smart Citation